Finance and Development, March 1970. (Finance and Development; Finance and Development, 1970)
This paper discusses achievement and failure of science in increasing world animal production. The paper highlights that the application of modern animal production technology is virtually confined to Western Europe, to the North American continent, to Australia, New Zealand, and Japan. The new technologies are not yet used in other parts of the world. Hardly more than a handful of their farmers have any knowledge or understanding of production methods commonplace in highly developed countries.